The Healthy and Hygienic Behavior: Analytical from Social Construction Perspective - Muria Herlina (Asian Social Work Journal, 2018)
This research aimed to find out the healthy and hygienic behavior at the Lebong County Bengkulu Province regarding on external and internal environment, objective judgment, baby delivery, breastfeeding, toilet, and the domestic non-smoking prohibition. The qualitative approach was used with subjects of the research were 16 housewives, with purposive sampling method applied, and 15 key informants who hold either formal or non-formal authority in the society. The data were obtained through in-depth interviews, observations and documentations. The results showed that the social reality in terms of baby delivery stemmed both from primary socialization (family: grandmother, mother and mother in law) and secondary socialization (internalization or education) that had become a tradition from one generation to the next generation. Another interesting fact is that a great number of mothers do not breastfeed their baby. Instead, they started to give supplements food to their 3-and-4- month old babies, such as water and honey, water and sugar, or rice porridge with coconut sugar. The community also seemed to be unfamiliar with the concept of healthy toilet as they fulfill the call of Mother Nature in random places, such as in the river, behind the trees, or in the sewer. Furthermore, it is not an easy task to have a non-smoking prohibition in every single family since smoking has become an externalized habit and a symbol of masculinity. The researcher concluded that the healthy and hygienic behavior was heavily influenced by a stock of knowledge derived either from the primary source (family) or from the secondary source (significant influence from key figures or education). Other factors that also had a great influence upon the implementation of the healthy and hygienic behavior in the society were poverty, distance and location, healthy facilities, and communal habits.